Multiple Functionally Redundant Signals Mediate Targeting to the Apicoplast in the Apicomplexan Parasite Toxoplasma gondii - Harb, Omar S. (American Society for Microbiology, 2004)
Most species of the protozoan phylum Apicomplexa harbor an endosymbiotic organelle—the apicoplast—acquired when an ancestral parasite engulfed a eukaryotic plastid-containing alga. Several hundred proteins are encoded in the parasite nucleus and are posttranslationally targeted to the apicoplast by a distinctive bipartite signal. The N-terminal 20 to 30 amino acids of nucleus-encoded apicoplast targeted proteins function as a classical signal sequence, mediating entry into the secretory pathway. Cleavage of the signal sequence exposes a transit peptide of variable length (50 to 200 amino acids) that is required for directing proteins to the apicoplast. Although these peptides are enriched in basic amino acids, their structural and functional characteristics are not well understood, which hampers the identification of apicoplast proteins that may constitute novel chemotherapeutic targets. To identify functional domains for a model apicoplast transit peptide, we generated more than 80 deletions and mutations throughout the transit peptide of Toxoplasma gondii ferredoxin NADP(+) reductase (TgFNR) and examined the ability of these altered transit peptides to mediate proper targeting and processing of a fluorescent protein reporter. These studies revealed the presence of numerous functional domains. Processing can take place at multiple sites in the protein sequence and may occur outside of the apicoplast lumen. The TgFNR transit peptide contains at least two independent and functionally redundant targeting signals, each of which contains a subdomain that is required for release from or proper sorting within the endoplasmic reticulum. Certain deletion constructs traffic to multiple locations, including the apicoplast periphery, the rhoptries, and the parasitophorous vacuole, suggesting a common thread for targeting to these specialized compartments.